Harmony of Q.S Az-Zumar and Earth Rotational Movement Science Materials in Elementary Schools Supporting Independent Learning: An Analytical Study - Nasution, Aida Rahmi; Husein, Muhammad; Syarfuni, Syarfuni (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
This research explores Q.S. Az-Zumar and science in analyzing Earth Movement material in elementary school books. This studyÂ  aims to investigates the suitability of the meaning contained in Q.S Az-Zumar and the Earth's rotational movement Science material. This study uses a qualitative approach and content analysis method. The data collection technique used a checklist sheet. Data analysis followed the flow of Mestika Zed (2004), namely reading, classifying, coding, formulating hypotheses, and drawing conclusions. The results found that the concept of the earth's rotational movement in Elementary School Science materials aligned with the idea of Q.S Az-Zumar. Science learning in elementary schools is in accordance with the curriculum, and its application does not conflict with the understanding and value of Islamic normativity. The recommendation is that educational practitioners can study more about the verses of the Qur'an to prove factually or contextually according to science.